Recent Advances in the Tandem Cyclization/Cycloaddition of Allene Intermediates from Copper-Catalyzed Cross-Coupling of Diazo Compounds with Terminal Alkynes - Chen, Nuan; He, Min; Zhou, Ting; Zhu, Yuqi; Zhang, Hong; Peng, Shiyong (Synthesis, 2020)
This short review summarizes the most recent developments (since 2010) in the tandem cyclization/cycloaddition of allene intermediates, generated from the copper-catalyzed cross-coupling of diazo compounds with terminal alkynes, to afford cyclic compounds.1 Introduction2 Cyclization2.1 Cyclization with Nucleophiles2.2 Cyclization with Electrophiles2.3 6π-Electrocyclization2.4 Other Cyclization3 Cycloaddition4 Conclusion
Keywords: copper catalysis; diazo compound; terminal alkyne; allene intermediate; cyclization; cycloaddition